Improving Students’ Reading Comprehension By Using Questioning Techniques In Narrative Text - Yessica Elisabeth Sibarani (Pascasarjana Universitas HKBP Nommensen, 2022)
This study attempts to improve students’ reading comprehension by using questioning technique.This study was conducted by applying classroom action research. The subject of the research wasclass X-4 SMA N.1 Sei Rampah which consisted of 30 students. The research was conducted intwo cycles, cycle I of three meeting and cycle II consisted of three meetings. The instruments forcollecting data were quantitative data namely reading comprehension test and qualitative datanamely, diary notes, observation sheet and questionnaire. Based on reading comprehension testscores, students score kept improving in every test of reading. Based on diary notes, observationsheet and questionnaire sheet it was found that the students were active and enthusiastic in learningreading through questioning techniques. The result of the research showed that questioningtechniques significantly improved students’ achievement in reading comprehension.